The beneficial effects of traditional Chinese medicine on antioxidative status and inflammatory cytokines expression in the liver of piglets - Wang, Xiaoyu; Wang, Yun; Mao, Yaqin; Hu, Aiming; Xu, Tianfang; Yang, Yan; Wang, Feibing; Zhou, Guangbin; Guo, Xiaowang; Cao, Huabin; Yang, Fan (Frontiers in Veterinary Science, 2022)
Oxidative stress and inflammation seriously affected the growth and development of piglets. Traditional Chinese medicine (TCM) prescriptions has been used to prevent various diseases of piglets, including anti-inflammatory and antioxidant. Here, we identified the effects of Xiao-Jian-Zhong-Tang (XJZT) and Jingsananli-sepsis (JJS) on the oxidative stress and inflammatory in the liver of piglets. The piglets were fed with the basal diet (Control group), basal diet affixed with 10 g/kg XJZT (TCM Ⅰ group), and basal diet affixed with 3 g/kg JJS (TCM Ⅱ group), respectively. The serum was gathered on days 30 and 60 and the liver samples were also collected on day 60. Results showed that the TCM Ⅰ and TCM Ⅱ markedly increased the activities of the glutathione peroxidase (GSH-Px) and total antioxidant capacity (T-AOC), and reduced the levels of malonaldehyde (MDA), TNF-α, IL-6, and IL-8 in serum. In addition, compared to the control group, Nrf2, SOD-1, NQO-1, and HO-1 mRNA expression levels and the protein levels of Nrf2 and HO-1 were significantly increased while NF-κB, TNF-α, IL-6, and IL-8 mRNA expression levels and the phosphorylation levels of NF-κB and IκB-α were decreased in TCM Ⅰ and TCM Ⅱ groups. Collectively, these findings suggested that TCM Ⅰ and TCM Ⅱ could enhance anti-oxidative and anti-inflammatory capabilities in the liver of piglets via the Nrf2/NF-κB pathway, providing a basis for the functional exploration of TCM prescriptions.